2013
DOI: 10.3389/fonc.2013.00137
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Curcumin Inhibits Proliferation of Esophageal Adenocarcinoma Cells and Enhances the T Cell Mediated Immune Response

Abstract: In Western countries the incidence of the esophageal adenocarcinoma (EAC) has risen at a more rapid rate than that of any other malignancy. Despite intensive therapies this cancer is associated with extreme high morbidity and mortality. For this reason, novel effective therapeutic strategies are urgently required. Dendritic Cell (DC)-based immunotherapy is a promising novel treatment strategy, which combined with other anti-cancer strategies has been proven to be beneficial for cancer patients. Curcumin (difer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…In agreement with these results, curcumin suppresses metastatic breast cancer in mice by increasing M1 and decreasing M2 macrophage populations in the TME, resulting in decreased STAT3, IL‐10, and arginase I gene expression and secretion . Another study revealed that curcumin nanoparticles upregulate the expression of the costimulatory molecule CD86 in DCs and decrease the secretion of proinflammatory cytokines (IL‐1β, IL‐6, IL‐8, IL‐10, and tumor necrosis factor α [TNF‐α]) from activated T cells, leading to their enhanced cytolytic ability against esophageal adenocarcinoma cells . Finally, curcumin, in combination with adoptive T‐cell therapy, restrains tumor growth and extends the survival of melanoma xenografted mice by enhancing the cytotoxicity of CTLs against tumor cells.…”
Section: Natural Compounds Possessing Epigenetic Properties That Stimsupporting
confidence: 53%
See 1 more Smart Citation
“…In agreement with these results, curcumin suppresses metastatic breast cancer in mice by increasing M1 and decreasing M2 macrophage populations in the TME, resulting in decreased STAT3, IL‐10, and arginase I gene expression and secretion . Another study revealed that curcumin nanoparticles upregulate the expression of the costimulatory molecule CD86 in DCs and decrease the secretion of proinflammatory cytokines (IL‐1β, IL‐6, IL‐8, IL‐10, and tumor necrosis factor α [TNF‐α]) from activated T cells, leading to their enhanced cytolytic ability against esophageal adenocarcinoma cells . Finally, curcumin, in combination with adoptive T‐cell therapy, restrains tumor growth and extends the survival of melanoma xenografted mice by enhancing the cytotoxicity of CTLs against tumor cells.…”
Section: Natural Compounds Possessing Epigenetic Properties That Stimsupporting
confidence: 53%
“…68 Another study revealed that curcumin nanoparticles upregulate the expression of the costimulatory molecule CD86 in DCs and decrease the secretion of proinflammatory cytokines (IL-1β, IL-6, IL-8, IL-10, and tumor necrosis factor α [TNF-α]) from activated T cells, leading to their enhanced cytolytic ability against esophageal adenocarcinoma cells. 69 Finally, curcumin, in combination with adoptive T-cell therapy, restrains tumor growth and extends the survival of melanoma xenografted mice by enhancing the cytotoxicity of CTLs against tumor cells. It is noteworthy that the enhanced antitumor response elicited by curcumin, other than a depletion of Tregs and TGF-β secretion, was caused by the downregulation of IDO expression in melanoma cells.…”
Section: Curcuminmentioning
confidence: 99%
“…According to them, the nanoformulation does not result in lung accumulation and thus increases overall systemic curcumin exposure. Nanocurcumin also inhibits proliferation of esophageal adenocarcinoma cells and enhances the T cell mediated immune response (Milano et al, ). Our study also suggests that nanocurcumin more effectively ameliorates nicotine‐induced toxicities through normalizing the function of the hepato‐functional enzymes, kidney function parameters, lipid profiles, anti‐oxidant status, and maintaining the structural integrity of different tissues under nicotine stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown that MA could retard the growth of other GI tract cancer cells such as esophagus, stomach or pancreatic cancer cells. Human esophageal squamous cancer cell line, OE33; gastric cancer cell line, SGC-7901; and pancreatic cancer cell line, Panc-1, have been widely used for anti-cancer studies to investigate the apoptotic effects and possible mechanisms of certain compounds (Li et al, 2012;Milano et al, 2013;Zhang et al, 2013). In our present study, these cancer cell lines were used as representative cell lines for esophageal cancer, gastric cancer and pancreatic cancer, respectively, to evaluate the potential of MA as an anti-GI tract cancer agent.…”
Section: Introductionmentioning
confidence: 99%